대리인문제와 외부감시주체가 여성의 이사회 참여에 미치는 영향 - 이상철; 이윤근; 문창진 (경영학연구, 2021)
This study examines the effects of agency problems and outside monitors on the participation of female directors on the board of directors. Analyzing 3,540 non-financial firm-year data listed on the Korea Stock Exchange from 2014 and 2018, we find that women's participation on the board of directors increases in the case of non-owner managed firm with high agency problems between shareholders and managers. We also unveil that when the monitoring incentives of outside monitors such as outside directors, foreign investors and institutional investors increase, the participation of female directors on the board of directors is likely to increase. Furthermore, analyzing 368 non-financial firm-year data of female directors on the board of directors, we find that non-owner manager, affiliated firm of large business groups, the ratio of outside directors on the board of directors and the ownership of both foreign investors and institutional investors have a positive effects on the characteristics of female directors such as the existence of female outside directors, expertise, attendance rate and tenure. The test results of this study indicate that if either agency problems or monitoring incentives of outside monitors are higher, the participation of female directors on the board of directors is likely to increase.
Keywords: agency problem; outside monitors; the participation of female directors on the board; characteristics of female directors.